A National Program for Certifying Physician's Assistants [The National Board Examiner, October 1972] - National Board of Medical Examiners (National Board of Medical Examiners, 1972)
This article appearing in the October 1972 issue of The National Board Examiner provides an overview of actions and steps taken by the National Board of Medical Examiners to produce a "national program to certify assistants to the primary care physician." The list of members of a Special Study Committee under the chair of Edmund D. Pellegrino, MD, is cited along with the committee's charge and responsibilities. In an article titled "At NBME Headquarters" it is noted that Barbara J. Andrew, Ph.D., "will have major responsibility in studying appropriate methodology for a new certifying examination for assistants to primary care physicians."